تقويم أداء الموظف العام في ضوء قانون الخدمة المدنية رقم 81 لسنة 2016 ولائحته التنفيذية: دراسة مقارنة - أحمد، منى أحمد حسين (جامعة جنوب الوادي - كلية الحقوق بقنا, 2021)
لما كانت الجهة الإدارية تعد نماذج تقويم أداء العاملين بها بما يتفق وطبيعة كل وحدة إدارية على حده وبما يتناسب مع نشاط ونوعية أهدافها. وكان بحثنا يقوم على أساس تقويم الموظف العام بمعيار الأداء العادي بما يستوجب على الموظف أداء عمله وإتمامه بكل دقه وتبصر وحرص وأن يراعى فيها واقعية وموضوعية التقويم بحيث يكون مبنيا على أساس الدقة التامة في قياس أداء وسلوك الموظف وعلى أن يراعى الحيادية التامة في التقييم وعدالة المعادلة بحيث يكون مبنيا على أساس التجرد من العلاقات الشخصية ومؤثراتها للوصول إلى المنحنى الأمثل للأداء وطبيعة كل وظيفة استنادا إلى معايير موضوعية عدة كالسلوك والجودة والتميز والإبداع والقدرة على تحمل المسئولية. Whereas the administrative authority prepares models for evaluating the performance of its employees in accordance with the nature of each administrative unit separately and as appropriate to the activity and quality of its objectives. Our Search was based on the evaluation of the public official with normal performance standard which requires that the employee has to perform and complete his work accurately, diligently, and carefully, and take into account the realism and objectivity of the evaluation so that it should be based on complete accuracy in measuring the employee’s performance and behavior and to take into account complete neutralism in the evaluation and the fairness of the equation so that it should be based on abstractness from personal relationships and their influence curve and the nature of each job according to several objective criteria such as behavior, quality, excellence, creativity and the ability to afford responsibility.
Keywords: الموظف العام -- التنمية المهنية -- تقويم الأداء -- القوانين الإدارية